PENGARUH HASIL BELAJAR KEWIRAUSAHAAN DAN PRAKTEK KERJA INDUSTRI TERHADAP MINAT BERWIRAUSAHA SISWA JURUSAN KRIYA KREATIF BATIK DAN TEKSTIL DI SMK NEGERI 8 PADANG - Yelvi Yanti; Yusron Wikarya (Serupa The Journal of Art Education, 2020)
This study aims to determine: (1) the effect of leaming outcomes of entrepreneurial eyes on  entrepreneurial interest in the creative craft deparment of batik and textiles and textiles at at SMK Negeri 8 Padang, (2) the effect of learning outcomes from industrial work practice on entrepreneurial interest majoring in batik and textile creative crafts at SMK Negeri 8 Padang. This study uses a correlation research method. : (1) The results of the analysis using simple linear regression explain that entrepreneurial learning outcomes have a significant and positive impact on interest in entrepreneurship. The results of this test give a correlation coefficient of 0.247> 0.159 a coefficient of determination of 0.061 and a value of 1.508 <1.659 a significant value of 0.000 with a probability of below = 5%. (2) The results of simple linear regression analysis provide practical learning outcomes that have a significant and positive impact on interest in entrepreneurship. The results of this test provide a correlation coefficient of 0.204> 0.159 coefficient of determination 0.042 and a value of 1.234 <1.659 with a significance value of 0.000 or a probability below = 5%.Keywords: Entrepreneurship learning outcomes, industrial work practices, Entrepreneurial Interests